Chlorine distribution management for spectrally stable and efficient perovskite blue light-emitting diodes. (January 2021) - Zhang, Feng; Zhang, Xin; Wang, Chenhui; Sun, Mengna; Luo, Xiyu; Yang, Yingguo; Chang, Shuai; Zhang, Dongdong; Duan, Lian
Abstract: Blue emitting perovskite electroluminescent (EL) devices are mainly realized based on chlorine mixing in bromide perovskites including CsPbBr3, CH3 NH3 PbBr3 (MAPbBr3 ), and CH(NH2 )2 PbBr3 (FAPbBr3 ). However, the inhomogeneous distribution and varied mobility of Cl − and Br − ions in alloyed perovskite films always result in EL spectra gradually shifting from blue to green region during device operation. Herein, alloyed FAPbBr3−x Clx nanocrystal (NC) films with optimized Cl distribution are fabricated through employment of Cl terminated amine ligands (Cl-ligands). The as fabricated FAPbBr3−x Clx NC films exhibit a Cl rich surface and 9 nm blue shifted emission spectrum compared to FAPbBr3−x Clx films fabricated by conventional Br terminated ligands (Br-ligands). Furthermore, EL devices based on Cl-ligands achieve blue EL emissions with maximum luminance of 2810 cd/m 2 and EQE of 3.1%, which is almost three times higher than that of EL devices based on Br-ligands. Importantly, Cl-ligands derived EL devices show greatly enhanced spectra stability with only slightly red-shifted EL spectra during device operation in a wide bias range, providing an alternative strategy for spectrally stable perovskite blue light-emitting diodes. Graphical Abstract: ga1 Highlights: FAPbBr3–x Clx NC films with optimized Cl distribution were fabricated by employment of Cl-ligands. The using of Cl-ligands resulted in 9 nm blue-shifted PL and nearly 1.6 fold enhanced E b for FAPbBr3–x Clx NCs. EL devices based on Cl-ligands achieved a significantly improved device performance compared to that of Br-ligands. The suppressed Cl migration was also demonstrated, which clarified the mechanism for enhanced spectra stability.